2000
DOI: 10.2514/3.14562
|View full text |Cite
|
Sign up to set email alerts
|

Influence of random excitations on acoustic instabilities in combustion chambers

Abstract: Although ows in combustors contain considerable noise, arising from several kinds of sources, there is a sound basis for treating organized oscillations as distinct motions. That has been an essential assumption incorporated in virtually all treatments of combustion instabilities. However, certain characteristics of the organized or deterministic motions seem to have the nature of stochastic processes. For example, the amplitudes in limit cycles always exhibit a random character, and even the occurrence of ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…When stochastic forcing is present, probability density functions (PDFs) have been used to describe the response of thermoacoustic systems in both experiments and theory [2,15,[18][19][20]. These papers show that a single periodic solution creates a bimodal PDF, and that the addition of other stable solutions creates additional peaks.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…When stochastic forcing is present, probability density functions (PDFs) have been used to describe the response of thermoacoustic systems in both experiments and theory [2,15,[18][19][20]. These papers show that a single periodic solution creates a bimodal PDF, and that the addition of other stable solutions creates additional peaks.…”
Section: Figurementioning
confidence: 99%
“…Various types of noise have been shown to destabilise systems that are linearly stable when noiseless [2,[13][14][15] . Noise resulting from entropy and vorticity has also been shown to play a part in the process [2].…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Experiments by Ma et al [20] have suggested that the velocity coupling function has a threshold nature, i.e., there is a threshold value of the acoustic velocity below which the effects of nonlinear combustion are not felt. In a recent paper, using a four-mode truncation and an ad hoc threshold velocity coupling model, Burnley and Culick [21] have computed a bifurcation diagram which shows triggered limit cycles. Additional results are available in the thesis by Burnley [22].…”
Section: Introductionmentioning
confidence: 99%